SPLASH-SXDF multi-wavelength photometric catalog - Mehta, V; Scarlata, C; Capak, P; Davidzon, I; Faisst, A; Hsieh, B; Ilbert, O; Jarvis, M; Laigle, C; Phillips, J; Silverman, J; Strauss, M; et al. (American Astronomical Society, 2018)
We present a multi-wavelength catalog in the Subaru/XMM-Newton Deep Field (SXDF) as part of the Spitzer Large Area Survey with Hyper-Suprime-Cam (SPLASH). We include the newly acquired optical data from the Hyper-Suprime-Cam Subaru Strategic Program, accompanied by IRAC coverage from the SPLASH survey. All available optical and near-infrared data is homogenized and resampled on a common astrometric reference frame. Source detection is done using a multi-wavelength detection image including the u-band to recover the bluest objects. We measure multi-wavelength photometry and compute photometric redshifts as well as physical properties for ~1.17 million objects over ~4.2 deg2, with ~800,000 objects in the 2.4 deg2 HSC-Ultra-Deep coverage. Using the available spectroscopic redshifts from various surveys over the range of 0 < z < 6, we verify the performance of the photometric redshifts and we find a normalized median absolute deviation of 0.023 and outlier fraction of 3.2%. The SPLASH-SXDF catalog is a valuable, publicly available resource, perfectly suited for studying galaxies in the early universe and tracing their evolution through cosmic time.